Identification of antennal alternative splicing by combining genome and full-length transcriptome analysis in Bactrocera dorsalis - Wang, Qi; Zhang, Jie; Liu, Chenhao; Ru, Chuanjian; Qian, Qian; Yang, Minghuan; Yan, Shanchun; Liu, Wei; Wang, Guirong (Frontiers in Physiology, 2024)
Alternative splicing is an essential post-transcriptional regulatory mechanism that diversifies gene function by generating multiple protein isoforms from a single gene and act as a crucial role in insect environmental adaptation. Olfaction, a key sense for insect adaptation, relies heavily on the antennae, which are the primary olfactory organs expressing most of the olfactory genes. Despite the extensive annotation of olfactory genes within insect antennal tissues facilitated by high-throughput sequencing technology advancements, systematic analyses of alternative splicing are still relatively less. In this study, we focused on the oriental fruit fly (Bactrocera dorsalis), a significant pest of fruit crops. We performed a detailed analysis of alternative splicing in its antennae by utilizing the full-length transcriptome of its antennal tissue and the insect's genome. The results revealed 8600 non-redundant full-length transcripts identified in the oriental fruit fly antennal full-length transcriptome, spanning 4,145 gene loci. Over 40% of these loci exhibited multiple isoforms. Among these, 161 genes showed sex-biased isoform switching, involving seven different types of alternative splicing. Notably, events involving alternative transcription start sites (ATSS) and alternative transcription termination sites (ATTS) were the most common. Of all the genes undergoing ATSS and ATTS alternative splicing between male and female, 32 genes were alternatively spliced in protein coding regions, potentially affecting protein function. These genes were categorized based on the length of the sex-biased isoforms, with the highest difference in isoform fraction (dIF) associated with the ATSS type, including genes such as BdorABCA13, BdorCAT2, and BdorTSN3. Additionally, transcription factor binding sites for doublesex were identified upstream of both BdorABCA13 and BdorCAT2. Besides being expressed in the antennal tissues, BdorABCA13 and BdorCAT2 are also expressed in the mouthparts, legs, and genitalia of both female and male adults, suggesting their functional diversity. This study reveals alternative splicing events in the antennae of Bactrophora dorsalis from two aspects: odorant receptor genes and other types of genes expressed in the antennae. This study not only provides a research foundation for understanding the regulation of gene function by alternative splicing in the oriental fruit